Apatinib targets both tumor and endothelial cells in hepatocellular carcinoma. (14th August 2018) - Yang, Chaoxu; Qin, Shukui
Abstract: Hepatocellular carcinoma (HCC) is one of the most commonly diagnosed malignancies worldwide with poor prognosis and tends to be hypervascular. Aberrant expression of the vascular endothelial growth factor 2 (VEGFR‐2) has been implicated in the progression of HCC and represents a valid target for anticancer therapy. Apatinib, a small molecule inhibitor of VEGFR‐2 tyrosine kinase, shows strong antitumor activity in various tumors. This study is designed to evaluate the activity of apatinib on both human umbilical vein vascular endothelial cells (HUVECs) and HCC cell lines (in vitro and in vivo), and also to investigate the characteristics and possible mechanisms underlying these effects by molecular biology methods. Following the results in our study, apatinib inhibited phosphorylation of VEGFR‐2 in HUVECs and blocked in vitro endothelial cell migration and tube formation. Concentration‐dependent antiproliferative effects of apatinib were also observed in all 6 HCC cell lines including SK‐Hep‐1, HepG2, Hep3B, Huh‐7, PLC/PRF/5, SMMC‐7721. Moreover, response to apatinib of HCC cell lines was significantly correlated with VEGFR‐2 expression level. Additionally, apatinib significantly inhibit VEGF‐triggered VEGFR‐2 phosphorylation and activation of downstream signaling molecules such as Akt and ERK1/2 in HCCs. Apatinib can also induce a cell cycle arrest at G2/M phase and promote HCC apoptosis tested in vitro. In vivo data showed that apatinib can effectively inhibit tumor growth, decreased angiogenesis, as well as induced HCC apoptosis (in some tumors), and thus prolonged animal survival in a mouse xenograft model of human HCC. Our findings suggested that apatinib is a highly potent, oral active anti‐angiogenic, and anti‐HCC agent. The results from current study provide a clear biological rationale to evaluate apatinib as a new agent in HCC in clinical setting, especially for the VEGFR‐2 overexpression ones. Abstract : This study indicated that apatinib showed antitumor activity in Hepatocellular Carcinoma (HCC) by targeting on both endothelial and tumor cells. Apatinib blocked in vitro endothelial cell migration and tube formation. In addition, apatinib significantly inhibited cell proliferation in 6 HCC cell lines in a concentration‐dependent manner. Apatinib could also induce a cell cycle arrest at G2/M phase of HCC and promote HCC apoptosis. Our findings suggested that apatinib is a highly potent, oral active anti‐angiogenic, and anti‐HCC agent.